Experimental and numerical investigation of thermal performance of channels with staggered array-based dimples - Xie Yong-Hui (Thermal Science, 2015)
Numerical simulation coupled with experimental method was carried out to study the flow and heat transfer characteristics in rectangular channel with staggered array-based dimples. The effect of different dimple depths and Reynolds number were investigated using the shear stress transport turbulent model coupled with gamma-theta transition model. The results indicated that heat transfer and flow resistance of the dimpled surface increases with the increase of dimple depth. Moreover, the thermal performance is sensitive to the flow transition. Heat transfer in each single dimple region increases monotonously in the streamwise direction with Reynolds number increasing. Heat transfer characteristics almost remain the same when the flow is under fully laminar or turbulent but increases greatly when the flow is transited from laminar condition to turbulent condition. Besides, the variations of friction coefficients and thermal performance coefficients are quite similar to those of heat transfer enhancement coefficients, which firstly increases then decreases with the increase of Reynolds number. By comparing the experimental and numerical results, it is found that staggered array-based dimples with δ/D = 0.2 was the most effective structure from the aspect of thermal performance.